’’ECOBRICK: SOLUSI KEATIF DAN INOVATIF PEMANFAATAN SAMPAH PLASTIK DI SEKOLAH” - Abbas, Ardiman Sudjiany; A. Syarifuddin, A. Syarifuddin; Idrus, Aderiza Cahya Ayu Restia; Fitriani, Fitriani; Sarah, Huria May; Utari, Ni’matul Aliyah Fajri; Fahmi, Nurul; Akhir, Muhammad; Paida, Andi (Penerbit Widina, Widina Media Utama, 2025)
The increasing problem of plastic waste in schools negatively affects cleanliness, health, and aesthetics, thereby requiring educational and innovative solutions. The Seminar “Ecobrick: Creative and Innovative Solutions in Utilizing Plastic Waste in Schools”, organized by students of the Teacher Professional Education (PPG) Program at Universitas Muhammadiyah Makassar, Batch 2 of 2024, majoring in Civic Education (PPKn), aimed to raise students’ awareness at SMP Negeri 1 Sungguminasa about plastic waste management through education and hands-on Ecobrick-making activities. The implementation consisted of three stages: planning, conducting the seminar and practical session, and reporting. The results showed an increase in participants’ knowledge and skills in processing plastic waste into functional products such as chairs, while supporting the implementation of the 3R (Reduce, Reuse, Recycle) concept at school. The seminar was attended by 40 eighth-grade students and OSIS members recommended by teachers. Evaluation results indicated that 85% of participants understood the concept of plastic waste processing and were able to produce Ecobricks independently. This activity had a positive impact in fostering environmental awareness and social responsibility, as well as serving as a concrete example of implementing Pancasila values through sustainable environmental action.ABSTRAKMasalah sampah plastik yang meningkat di lingkungan sekolah berdampak negatif terhadap kebersihan, kesehatan, dan estetika, sehingga diperlukan solusi edukatif dan inovatif. Kegiatan Seminar “Ecobrick: Solusi Kreatif dan Inovatif dalam Pemanfaatan Sampah Plastik di Sekolah” yang dilaksanakan oleh mahasiswa PPG Universitas Muhammadiyah Makassar Gelombang 2 Tahun 2024 bidang studi PPKn bertujuan meningkatkan kesadaran peserta didik SMP Negeri 1 Sungguminasa terhadap pengelolaan sampah plastik melalui edukasi dan praktik pembuatan Ecobrick. Pelaksanaan kegiatan meliputi tiga tahap, yaitu perencanaan, pelaksanaan seminar dan praktik, serta pelaporan. Hasil kegiatan menunjukkan peningkatan pengetahuan dan keterampilan peserta dalam mengolah sampah plastik menjadi produk fungsional berupa kursi, serta mendukung penerapan konsep 3R (Reduce, Reuse, Recycle) di sekolah. Seminar diikuti oleh 40 peserta didik kelas VIII dan anggota OSIS yang direkomendasikan guru. Berdasarkan hasil evaluasi, 85% peserta memahami konsep pengolahan sampah plastik dan mampu menghasilkan Ecobrick secara mandiri. Kegiatan ini berdampak positif dalam menumbuhkan kepedulian lingkungan, tanggung jawab sosial, serta menjadi wujud nyata penerapan nilai-nilai Pancasila melalui aksi peduli lingkungan berkelanjutan.